Dual regulatory effects of medical bovine collagen sponge on macrophages in vitro - Rui Wang; Yu Liu; Jingjing Chen; Zhu Meng; Weiye Ren; Wei Huang; Zhaoxu Wang; Qianqian Han (PLoS ONE, 2026)
Medical bovine collagen sponges (MBCS) are extensively utilized in clinical settings for hemostasis and tissue augmentation owing to their superior biocompatibility, biodegradability and hemostatic properties. Nevertheless, their immunomodulatory influence on macrophage function remains largely unexplored. In this study, we systematically evaluated the effects of MBCS on RAW264.7 macrophages through comprehensive in vitro assays, including proliferation analysis, phagocytosis assessment, cytokine expression and angiogenesis evaluation. Our results demonstrate that MBCS significantly enhances macrophage proliferation and phagocytic capacity while potently stimulating VEGF secretion. Furthermore, MBCS-conditioned macrophage supernatants markedly promote endothelial tubule formation in vitro. Notably, MBCS moderately promotes inflammatory responses in resting macrophages, whereas pretreatment with MBCS effectively inhibits lipopolysaccharide (LPS)-induced pro-inflammatory reactions, as reflected by reduced production of TNF‑α, nitric oxide and CD86. These findings reveal the effects of MBCS on macrophages at the cellular level, providing experimental evidence and mechanistic support for its tissue-repairing functions.